THE INFLUENCE OF PROMOTION, PRODUCT QUALITY, AND SERVICE QUALITY ON CUSTOMER SATISFACTION (CASE STUDY: ALODOKTER APPLICATION SERVICES) - Rizky Herdianto; Wahyudi David (Sean Institute, 2023)
Condition the COVID-19 pandemic pushes happening changes high-speed structure well in education as well as the world of health, for reduce potency the spread of Covid-19 of course push Lots activities carried out online included consultation health. Moment This delivering applications content health Lots looked at and in demand by the public teenagers and adults. This study aims to determine the effect of promotion, product, and service quality on customer satisfaction. Study This use approach quantitative with descriptive approach. Study quantitative termed with formal models. The population in study this that is user application Scattered medical doctors whole indonesian. Retrieval technique sample in research this use NonProbability Sampling. Research this use sample which is active individual in do consultation on the application HealthReplies.com in 3 months last. The results of this study stated that promotion influential positive significant to consumer satisfaction, quality product has influential positive significant to consumer satisfaction, quality service influential positive significant to consumer satisfaction. And promotion, quality product and quality service in a manner together influential positive significant to customer satisfaction.